PRANAKRUSHNA PARIJA: A FORGOTTEN SCIENTIST AND ACADEMICIAN - Pradhan, Chinmay; Bhattacharya, Neetu; Pushker, Kumar; Bhattacharya, Amit (SCHOOL SCIENCE, 2025)
This article explores the life and work of Pranakrushna Parija (1891–1978), an Indian scientist with international distinction whose contributions to plant science have profoundly impacted the world. He is regarded as a distinguished botanist and a great educationalist in the fields of plant science, education and humanitarian service. He received his initial scientific training at the University of Cambridge, England, under the guidance of eminent scientist Frederick Frost Blackman. Blackman and his lab conducted extensive research in plant physiology and plant photosynthesis. In 1928, Blackman and Parija discussed the changes in permeability that may be involved in fruit ripening. Together, both elucidated the intricate relationship between fruit ripening, oxygen tension and respiration in the context of an apple. The duo published several breakthrough papers highlighting their pioneering work in plant respiration, respiratory regulation in ripening apples and mechanisms of fruit ripening. After his return to India, he was appointed professor of botany at Ravenshaw College, Cuttack, India. With his wide experience as a distinguished researcher, educationalist and academician, he has held various academic and administrative roles in India. He carried a sense of commitment and keenness to the cause of science, education and the welfare of his countrymen, whom he served until his death.